Exploring the frozen frontier: unmanned aerial vehicles and multispectral sensors unveiling cryosphere dynamics in East Antarctica’s Dronning Maud Land - Geetha Priya M; Krishna Venkatesh (GIScience & Remote Sensing)
In this study, we investigated specific components and intra-seasonal dynamic processes that play pivotal roles in the East Antarctica’s central Dronning Maud Land (cDML) region. The present study focuses on harnessing the potential of a multispectral sensor-based Unmanned Aerial Vehicle (UAV) for cryosphere studies over the polar ice sheet in cDML (Schirmacher Oasis) region of East Antarctica, conducted as part of the 42nd and 43rd Indian Scientific Expedition to Antarctica (ISEA), under the aegis of National Centre for Polar and Ocean Research (NCPOR), Ministry of Earth Sciences, Government of India, during austral summer period from 2022 to 2023. The surveyed area (~100 acres) encompasses a segment of the ice sheet frontal edge outer margin, situated near the Maitri Indian research base at Schirmacheroasen, and includes a melt pond/supraglacial lake. The results indicate that the ice sheet frontal edge segment experienced a decrease in elevation of 0.25 meters with a total mass reduction of 13.6 kilotons during one-week period. The supraglacial lake accumulated meltwater with an average depth ranging from 0.25 to 1.6 meters, covering an area spanning from 9.1 × 103 square meters to 24.7 × 103 square meters. The ultra-high resolution multispectral UAV data also revealed dynamic changes in various cryo-facies classes, including water bodies/meltwater, frozen meltwater, dry and wet snow, debris/bare ice, and bedrock during the study period over the study area. This study represents a pioneering effort in assessing the region near the Maitri research base in both spatial and temporal scales. It also marks the first application of UAV surveying techniques with the integration of in-situ data from the Pressure Sensor Assembly (PSA) to examine and understand its complex intra-seasonal dynamics and characteristics. The research team is the first Indian group to employ UAVs for scientific research in the Antarctic region, which is a notable advancement in Indian scientific exploration and contributes to the expanding knowledge of the Antarctic region.